Changes in Film Representations of Sami Culture and Identity - Skarðhamar, Anne Kari (Nordlit, 2008)
My intention is to analyse changes in ideas and discursivestrategies in selected films from 1929 to 2007 as regardsrepresentations of Sami culture and Sami identity in Finnmark. In different ways the films indicate a conflict of cultures and point to problems of exploitation of indigenous peoples, which may be regarded as part of Nordic colonialism.The emphasis will be on Lajla (1929) and the prize-winningVeiviseren (1987). The story of the young girl Lajla is told from a non-Sami point-of-view, and the mode of representation of otherness is of importance. In 1937 an abbreviated version of Lajla by the same director was presented, and a comparison of the two versions will show changes in the representation of ethnicity. Per Høst's narrative documentaries Same-Jakki (1957) and SamiÆllin (1972), seen from an ethnic Norwegian perspective, will briefly be discussed and compared to the ideas and discourse in Lajla.The action film Veiviseren (The Guide) (1987) by Nils Gauprepresents a totally different perspective by focusing on power relations, religious attitudes and ethical values. The language of the film is Sami. Finally, Gaup's most recent film, Kautokeinoopprøret (Kautokeino riot) (2007), a narrative based on historical events, will be briefly discussed.
Keywords: Film; samisk kultur; samisk identitet; Nils Gaup; Per Høst; Lajla; Veiviseren; Kautokeinoopprøret; Nordic Colonialism